STRATEGI KOMUNIKASI PRAJURU DESA ADAT DALAM PENCEGAHAN PENYALAHGUNAAN NARKOBA DI KALANGAN REMAJA DESA PEMOGAN DENPASAR SELATAN - I Made Sinardika; I Dewa Ayu Hendrawathy Putri; Wayan Sukabawa (Anubhava: Jurnal Ilmu Komunikasi HIndu, 2023)
This study describes Prajuru Traditional Village communication strategies in preventing drug abuse among adolescents in Pemogan Village, South Denpasar. The city of Denpasar, precisely in the South Denpasar sub-district, is the largest number of drug abusers that can be uncovered by the authorities. The impact of drug abuse does not only threaten the survival and future of those who abuse it, but also the future of the nation and state. The purpose of this research is for teenagers to be more aware of and avoid drug abuse amid the current scourge of globalization and modernization. This type of research is qualitative research that seeks to describe social phenomena that are developing in the masses today and then described based on the concepts and theories of persuasive communication, S-O-R communication theory and interpersonal communication.                 The results of this study are Prajuru Traditional Village can prevent drug abuse among youth in Pemogan Village, South Denpasar by using Persuasive communication strategies, Strengthening Religious Cultural Values ​​and Providing customary sanctions for drug abuse according to the anti-drug Pararem. Meanwhile, the obstacles of Prajuru Traditional Village in preventing drug abuse among youth in Pemogan village, South Denpasar are: Bad stigma associated with drugs is a problem that becomes an obstacle in efforts to deal with drug abuse, Lack of Resources, Low Community Participation, Lack of Educational Information and Limited Budget. And the implications for preventing drug abuse among youth in Pemogan village, South Denpasar, namely: Increasing Youth Awareness about the Dangers of Drugs, Increasing Youth Skills in Solving Problems, Increasing Community Involvement, Creating a Safe and Healthy Environment, There is a decrease in drug abuse cases among Pemogan village youth.